PERANAN SENTRAL GURU AGAMA HINDU DALAM PENCAPAIAN TUJUAN PENDIDIKAN NASIONAL DI INDONESIA DAN PEMBANGUNAN KARAKTER BANGSA YANG BERAKHLAK MULIA, JUJUR, TERAMPIL, BERHATI SUCI DAN BERSIH LAHIR BATIN - Selasih, Ni Nengah (LPM IHDN Denpasar, 2015)
The teachers of Hindu religion classes play central role in the effort to reach the goal of the national education as well as to build the characters that include honesty, skillfullness, clean and good-heartedness, as described in the national standard of education regulation No 20/2003 in which it states that the curriculum has to provide religious education (Pasal 37 UU Sisdiknas). The government attention to the education is implemented too by the issue of the Regulation on Teachers and Lecturers which states that teachers are professional educators with main duty to educate, teach, guide, train, and evaluate the students in the formal elementary, secondary, and high schools (UU RI No. 14/2005) Purwanto (2004:10).Education is the intentional enlightening from the adult to the younger ones in relation to their development in order to make them useful for themselves and in the societyâThe Indonesian national education systemas stated in UU No.2/1989 Bab, II, pasal 4,Â states that the goal of the education is to develop a complete Indonesia people who are religious, good in their characters, have good knowledge and skills, healthy physically and mentally, independent, responsible for the society and nation. In line with that, the Hindu teachers should refer to the Vedic teachings and consider the physical, psychological, and social environments of study, the life as students (Sisya/Brahmacari), their roles (Acarya), the curriculum, the mteaching methods, as well as the goal of the education. These all should be centered on teaching with the emphasis on directing and motivating to reach the character buildingfacilitating that through learning experience helping to develop attitudes, values, and self adaptation At schools teachers should commit themselves to be 1) role models, 2) inspirators, 3) motivators, 4) regulator, 5) evaluator besides having good vision. Without these all, the goal of education will fail.